Fractal Characteristic of Electrical Trees Grown in Silicone Rubber under Environmental Stress - M. S. Mohd Fua’ad; M.H. Ahmad; Y. Z. Arief; N. A. Ahmad (International Journal of Electrical and Computer Engineering (IJECE), 2017)
One of the degradations of insulation is in the form of electrical treeing in which classified as a pre-breakdown phenomenon of electrical insulation. The electrical tree is commonly forming in the shape of tree-like or root-like which may have fractal structures. Due to this fractal structure, electrical treeing formation and patterns are analysed via fractal dimension and lacunarity to study the self-similarity patterns of electrical treeing. Many types of research have been conducted to study the fractal dimension and lacunarity of electrical treeing to fully understand the electrical tree mechanism and characteristics. However, fractal and lacunarity structures of